2007
DOI: 10.1007/s11237-007-0022-2
|View full text |Cite
|
Sign up to set email alerts
|

Complex investigation of cluster adsorbtion of water molecules on hydrophilic centers of graphite and graphitized thermal carbon black

Abstract: A complex theoretical-experimental investigation has been carried out on the interaction of water with hydrophilic centers -phenolic and carboxyl groups -on the surface of graphite and graphitized thermal carbon black in low surface occupation range. It is shown that microclusters, formed by the absorption on such centers, have a cyclic structure of 4-5 molecules similar to those observed in liquid water and on the surface of silver iodide. The formation of such structures is shown to be energetically advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…Our ab initio calculation showed that the higher-energy adsorption sites in the range of relative pressures studied are residual carboxyl groups of the lateral and basal surface of the graphite crystallites with adsorption energies equal to 43.6 and 40.2 kJ/mol, respectively [11]. The difference in these values is in very good accord with the difference in the positions of the maxima in Fig.…”
Section: Discussion Of the Calculation Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Our ab initio calculation showed that the higher-energy adsorption sites in the range of relative pressures studied are residual carboxyl groups of the lateral and basal surface of the graphite crystallites with adsorption energies equal to 43.6 and 40.2 kJ/mol, respectively [11]. The difference in these values is in very good accord with the difference in the positions of the maxima in Fig.…”
Section: Discussion Of the Calculation Resultssupporting
confidence: 78%
“…2d. This conclusion is supported also by the results of quantum-chemical calculations showing that the energy of the interaction of water molecules with vicinal OH groups on the silica gel surface is about 70 kJ/mol [12], while the energy of the interaction of water molecules with carboxyl groups of the carbon surface is much lower, about 40 kJ/mol [11]. In the relative pressure range studied, adsorption occurs on the first type of sites.…”
Section: Discussion Of the Calculation Resultssupporting
confidence: 65%
“…41,42 The acidic carboxyl groups are strongest with respect to the hydrogen bond, near 15-20 kJ mol À1 . 43,44 The hydroxyl group in carboxyl is stronger than in phenols with respect to its protondonor ability and polarity of the O-H bond. The carbonyl group is stronger than the oxygen-containing group in esters and ethers.…”
Section: Surface Chemistrymentioning
confidence: 99%
“…The degree of coverage of the hydrophobic surface of graphitized thermal black (GTB) does not reach unity even at a pressure close to saturation [89], i.e., a conventional monolayer of water on the surface of this sorbent in the classical sense is not formed, although bulky water microclusters are formed on its residual active centers [86,92]. On account of intracluster interaction between the molecules the Q(a) relationship does not decrease, as for hydrophilic sorbents, but conversely increases with increase in coverage, reaching a maximum at P/P S ® 1.0 [89].…”
Section: Immersion Wetting Isothermsmentioning
confidence: 99%
“…The differential heats of adsorption of water on this sample, obtained in a direct calorimetric experiment, and the first quantum-chemical calculations of the energy of interaction of water molecules with the active centers of GTB were presented in [90]. The evolution of these investigations can be found in [91,92].…”
mentioning
confidence: 99%